Culture's Role in Successful Technology Transformation - Tyagi, Urvashi; Tyagi, Urvashi; Clearfield, Chris (MIT Sloan Management Review, 2021)
In this interview, the second in MIT Sloan Management Review's Leading With Impact series, Urvashi Tyagi discusses her role as CTO at ADP with coach and consultant Chris Clearfield. She also describes ADP's systems-first approach to its payroll and HR solutions business and shares what she has learned about creating a healthy corporate culture and evaluating employee performance.